Navigating Legal Pluralism in the Conflict Between Waqf and Customary Land in Indonesia - Sriutami, Rahayu; Rezki, Moch. Gufron Fajar (SASI, 2026)
Introduction: The dualism of land law in Indonesia (positive law, Islamic law, customary law) that causes conflicts, especially between waqf land and customary heritage land. Purposes of the Research: Analyze the roots of conflicts, implications for legal certainty, and find integrative solutions. Methods of the Research: The research uses a normative legal method with a descriptive-analytical approach through a literature study of laws and regulations, doctrines, and scientific literature related to agrarian law, waqf, and customary law community rights. Results of the Research: The results of the study show that disputes generally originate from differences in the concept of land ownership, where waqf law places land as an individual right that can be waqf for religious and social purposes, while customary law views land as a communal asset that has historical, cultural, and spiritual value so that any change in status must obtain the approval of all parties who are entitled to it. This paradigm difference causes the administrative recognition of the state to not always be in line with the social legitimacy that lives in indigenous peoples, thus giving rise to legal uncertainty and prolonged conflicts. This research emphasizes the importance of harmonizing agrarian law, Islamic law, and customary law through strengthening land status verification, optimizing waqf administration, involving customary institutions in the decision-making process, and increasing coordination between agencies. This approach is expected to be able to realize legal certainty that is not only formal, but also reflects substantive justice and maintains social harmony in the settlement of land disputes in Indonesia.